Seasonal arsenic in catfish (Siluriformes, Ariidae) and the hydrochemical conditions of two areas in a Ramsar site on the Brazilian coast - JULIANA S. AZEVEDO; ELISABETE S. BRAGA; LEONARDO S. KUNIYOSHI; DEBORAH INÊS T. FÁVARO (Anais da Academia Brasileira de Ciências, 2023)
Abstract The construction of a data bank concerning metal and metalloid content of bioindicator fish from coastal areas is very important as it can help environmental managers in decision making. In natural conditions, the concentration of elements can be influenced by abiotic parameters such as water salinity. In this study, catfish Cathorops spixii were evaluated concerning the total arsenic (As) concentration in the muscle tissues of individuals subjected to different abiotic conditions in the Cananéia-Iguape Estuarine-Lagoon Complex (CIELC), which was recently included on the Ramsar list of wetlands of international importance. Seventy-four catfish were seasonally caught in the northern and southern regions of the CIELC and their hydrochemical parameters were obtained. C. spixii from the southern, best preserved, area showed arsenic concentrations around ten times higher than the maximum limit established for fish intended for human consumption. However, these high concentrations of arsenic could be associated with the abiotic parameters of the water, such as salinity variations, in this area.